2014
DOI: 10.13040/ijpsr.0975-8232.5(4).1279-89
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Tuberose flower extracts were obtained by green technology of Supercritical carbon dioxide (SC-CO 2 ) extraction and solvent extractions (using n-hexane and petroleum ether of b.p. 60-80 °C). Antimicrobial activities of these extracts were tested in vitro against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Helicobacter pylori, Vibrio cholerae and Candida albicans. No activity was found against H. pylori and V. cholerae. Antimicrobial activities of the extracts were established by minimum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…The main volatile compounds from tuberose flowers were found predominantly at lower pressure extraction (18 MPa), while common compounds in supercritical plant extracts, as terpenes, alcohols, and some fatty acids were found in almost all extracts at different extraction pressures. Similar behavior was reported by Ghosh et al [4] and Gomes et al [18].…”
Section: Chemical Composition In Tuberose Flowerssupporting
confidence: 90%
See 4 more Smart Citations
“…The main volatile compounds from tuberose flowers were found predominantly at lower pressure extraction (18 MPa), while common compounds in supercritical plant extracts, as terpenes, alcohols, and some fatty acids were found in almost all extracts at different extraction pressures. Similar behavior was reported by Ghosh et al [4] and Gomes et al [18].…”
Section: Chemical Composition In Tuberose Flowerssupporting
confidence: 90%
“…Tuberose flowers yield extracts obtained at different pressure and temperature processes are shown in Table 1, and were different and higher than yields reported by Gosh et al [4], who reported a supercritical yield extraction of 0.5%. Yield extracts were even higher than those reported by Rakthaworn et al [2], who evaluated different extraction methods and reported yields of tuberose flowers extracts obtained by cold palm wax enfleurage, hot palm oil enfleurage, and solvent extraction with hexane and petroleum ether, obtaining yields of 0.3137%, 6.5808%, 0.0279%, and 0.0182% respectively.…”
Section: Supercritical Fluid Extractioncontrasting
confidence: 61%
See 3 more Smart Citations